Vaccine Development against the Renin-Angiotensin System for the Treatment of Hypertension - Tatsuhiko Azegami; Hiroshi Itoh (International Journal of Hypertension, 2019)
Hypertension is a global public health issue and the most important preventable cause of cardiovascular diseases. Despite the clinical availability of many antihypertensive drugs, many hypertensive patients have poor medication adherence and blood pressure control due, at least partially, to the asymptomatic and chronic characteristics of hypertension. Immunotherapeutic approaches have the potential to improve medication adherence in hypertension because they induce prolonged therapeutic effects and need a low frequency of administration. The first attempts to reduce blood pressure by using vaccines targeting the renin-angiotensin system were made more than half a century ago; however, at the time, a poor understanding of immunology and the mechanisms of hypertension and a lack of optimal vaccine technologies such as suitable antigen design, proper adjuvants, and effective antigen delivery systems meant that attempts to develop antihypertensive vaccines failed. Recent advances in immunology and vaccinology have provided potential therapeutic immunologic approaches to treat not only infectious diseases but also cancers and other noncommunicable diseases. One important biotechnology that has had a major impact on modern vaccinology is virus-like particle technology, which can efficiently deliver vaccine antigens without the need for artificial adjuvants. A human clinical trial that indicated the effectiveness and safety of a virus-like particle-based antiangiotensin II vaccine marked a turning point in the field of therapeutic antihypertensive vaccines. Here, we review the history of the development of immunotherapies for the treatment of hypertension and discuss the current perspectives in the field.